2022
DOI: 10.31234/osf.io/5r8mg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Not within spitting distance: salivary immunoassays of estradiol have subpar validity for predicting cycle phase

Abstract: Salivary steroid immunoassays are widely used in psychoneuroendocrinology to investigate the psychological effects of menstrual cycle phase. Though manufacturers advertise their assays as suitable, they have not been rigorously validated for this purpose. We collated data from eight studies across more than 1,200 women and more than 9,500 time points. All studies measured estradiol and progesterone and had at least one independent indicator of cycle phase (day in cycle relative to the luteinising hormone surge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…These values were imputed separately for the forward-counting and backward-counting methods. Arslan et al (2022) have previously demonstrated that estradiol and progesterone values imputed in this way using the forward-and backward-counting methods are highly correlated with values measured from serum (progesterone: r = .83 or .87, respectively; estradiol: r = .68 or .72, respectively). By contrast, Arslan et al (2022) reported that correlations between values from salivary immunoassays and from serum were substantially weaker.…”
Section: Data Collectionmentioning
confidence: 98%
See 3 more Smart Citations
“…These values were imputed separately for the forward-counting and backward-counting methods. Arslan et al (2022) have previously demonstrated that estradiol and progesterone values imputed in this way using the forward-and backward-counting methods are highly correlated with values measured from serum (progesterone: r = .83 or .87, respectively; estradiol: r = .68 or .72, respectively). By contrast, Arslan et al (2022) reported that correlations between values from salivary immunoassays and from serum were substantially weaker.…”
Section: Data Collectionmentioning
confidence: 98%
“…For each woman, the date of their last menses and the date for their next menses were used to calculate cycle day using both the backward-counting method and the forward-counting method. Cycle-day data were then used to impute progesterone and estradiol levels using an algorithm described in (and developed by) Arslan et al (2022). These values were imputed separately for the forward-counting and backward-counting methods.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary hormone radioimmunoassays like those used in our study were our method of choice due to the availability of funding and a specialized lab at our institution. Immunoassays, including radioimmunoassays, were criticized for yielding results inferior to other methods like serum analysis or tandem mass spectrometry, and seem to have low validity for example for estimating menstrual cycle phase (see empirical comparison of assessment methods by Arslan et al, 2022). Nevertheless, problems with measurement validity have been studied more intensively for enzymatic immunoassays (e.g., Welker et al, 2016b;see Chafkin et al, 2022, for an expansion of this work to chemiluminescent immunoassays, which seem to overestimate testosterone and cortisol and suppress testosterone sex differences when compared to LC-MS/MS).…”
Section: Limitations Of Salivary Immunoassaysmentioning
confidence: 99%